2000
DOI: 10.1111/j.1572-0241.2000.03252.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of cardiac function in cirrhotic patients with and without ascites

Abstract: Liver cirrhosis is associated with enlarged right cardiac chambers. Diastolic dysfunction and mild pulmonary hypertension are evident in cirrhotic patients with ascites. These changes do not depend on variations in the left ventricular geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(50 citation statements)
references
References 30 publications
7
42
1
Order By: Relevance
“…Our findings in this selected population further corroborate previous findings by other authors [13][14][15] and by our group [12], indicating that diastolic dysfunction is an expression of cardiac involvement paralleling progression of cirrhosis. Indeed our data, based on the historical comparison with the Framingham study [43] suggest that age, one of the components involved in the pathogenesis of diastolic dysfunction and possibly a misleading issue in previous investigations, can be excluded at least as a co-factor.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our findings in this selected population further corroborate previous findings by other authors [13][14][15] and by our group [12], indicating that diastolic dysfunction is an expression of cardiac involvement paralleling progression of cirrhosis. Indeed our data, based on the historical comparison with the Framingham study [43] suggest that age, one of the components involved in the pathogenesis of diastolic dysfunction and possibly a misleading issue in previous investigations, can be excluded at least as a co-factor.…”
Section: Discussionsupporting
confidence: 82%
“…This alteration is more marked in presence of ascites, presumably because the increased intrathoracic pressure and the bulging of the diaphragm, induced by abdominal fluid accumulation, interfere with the diastolic expansion of the ventricles [15]. It is present, however, even in absence of ascites, suggesting that non-mechanical factors are involved as well [12,3].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…There are conflicting data about the correlation between the presence of ascites in patients with liver cirrhosis and the prevalence of LV diastolic dysfunction [12,20,23]. In an earlier study, LV diastolic dysfunction in cirrhotics showed a significant improvement after total paracentesis in patients with tense ascites suggesting that LV diastolic dysfunction in these patients might be in part secondary to physical factors such as higher hemodynamic overload, increased intrathoracic pressure, and elevation of the diaphragm by abdominal fluid accumulation [24].…”
Section: Diastolic Dysfunction In Patients With Liver Cirrhosismentioning
confidence: 99%
“…[7,8,9,10] The prevalence and extent of systolic dysfunction in cirrhotic patients appear to be variable.…”
mentioning
confidence: 99%